2020
DOI: 10.1002/jso.26253
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of PRL3 expression with colorectal cancer progression

Abstract: Objectives: To evaluate the relationship between phosphatase of regenerating liver 3 (PRL3) expression and clinical outcome in colorectal cancer (CRC). Background: PRL3, a protein tyrosine phosphatase functions as one of the key regulatory enzymes of various signal transduction pathways. PRL3 is highly expressed in a majority of cancers and is a novel potential therapeutic target. Methods: PRL3 expression was evaluated by immunohistochemistry in 167 patients with CRC, 37 patients with no disease, and 26 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Furthermore, overexpression of stathmin has been reported to be associated with PI3Kinase activation in endometrial 37 and breast cancers 10 . We have also recently reported the significant positive correlation of PRL3 with activated Akt in metastatic colorectal cancer 5 . MAPK/PI3K and its downstream signaling components are critical for cancer cell proliferation and survival and are identified as hallmarks of cancer 38 .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Furthermore, overexpression of stathmin has been reported to be associated with PI3Kinase activation in endometrial 37 and breast cancers 10 . We have also recently reported the significant positive correlation of PRL3 with activated Akt in metastatic colorectal cancer 5 . MAPK/PI3K and its downstream signaling components are critical for cancer cell proliferation and survival and are identified as hallmarks of cancer 38 .…”
Section: Discussionmentioning
confidence: 84%
“…10 We have also recently reported the significant positive correlation of PRL3 with activated Akt in metastatic colorectal cancer. 5 MAPK/PI3K and its downstream signaling components are critical for cancer cell proliferation and survival and are identified as hallmarks of cancer. 38 In the present study, we demonstrated that high stathmin expression level positively correlated with Ki67 staining, a cell proliferation marker, and negatively correlated with apoptosis in mCRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, aberrant PI3K expression in metastatic tumors is not always associated with PIK3CA mutations, suggesting the involvement of other mechanisms. We have identified phosphatase of regenerating liver 3 (PRL3), an upstream marker of the PI3K/Akt pathway, and ezrin, and sodium‐hydrogen exchanger regulatory factor 1 (NHERF1), the downstream markers of PI3K/Akt signaling pathway in CRC 40–42 . These markers are highly expressed in mCRC with minimal expression in normal or premalignant adenoma 40–42 and might be potential targets for anti‐PI3K‐mediated targeted therapy.…”
Section: Genetic and Epigenetic Alterations: Impact On Signaling Path...mentioning
confidence: 99%
“…5 ). 140 Since PRL3 transcripts are overexpressed in CRC metastases found in the liver, and PRL3 expression cannot be detected in non-metastatic primary tumors and normal colorectal epithelium. PRL3-induced enhancement of EMT dependent on EGFR activation and PRL3 promoted cell invasion and upregulated MMPS by activating AKT in vitro and in vivo.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%